Riparian vegetation and their impact on the geomorphology of the Diyala River between alswaeed and Kharenabat - محمد سعيد, هالة (Al-Adab Journal, 2018)
The riparian plants had an effects and affected by the geomorphology of the river, it's have a crucial impact in the control of the river geomorphology and the changes in its properties and its dynamics operations, so in this research divided the kinds of the riparian plants, and statement of its positive, negative impacts on the banks, and discussed the relationship between them and the amount of discharge in the Diyala river course in the study area, and then discuss the relationship of the riparian plants and their impact on banks of river morphology and finally talking about the impact of human activity on the natural vegetation of the banks and their impacts in the study area.